Analisis Morfologi Integratif Ikan Berod (Mastacembelus unicolor) di Sungai Brantas, Jawa Timur - Ifa Sufaichusan; Septiana Sri Astuti; Akhsan Fikrillah Paricahya; Bela Fatma Hani Ayu Lestari; Kiki Nur Azam Kholil; Fisma Josara Apriliyanti; Ating Yuniarti; Maheno Sri Widodo; Wahyu Endra Kusuma (Postgraduate, University of Mataram, 2024)
Mastacembelus sp., a member of the Mastacembelidae family, is distributed across Java, Sumatera, and Kalimantan. Mastacembelus, locally named berod fish in the Brantas River lacks population’s descriptions and morphological analyses. Morphological analyses, including morphometric and meristic descriptions, are important for precise identification and classification of kinship relationships, serving as a cornerstone in the fields of biology, taxonomy, and conservation. This study aimed to conduct a comprehensive morphometric and meristic identification of the berod fish population in the Brantas River, East Java. A total of 37 samples were collected from 6 different locations: Blitar, Tulungagung, Kediri1, Kediri2, Nganjuk, and Mojokerto. The morphometric measurements were based on 25 characters, while the meristic calculations were based on 6 characters. The data analyzed with PCA and CA using SPSS and PAST programs. The results revealed that berod fish in the Brantas River had morphological characters belongs to the Mastacembelus unicolor. However, notable disparities were observed in meristic characters, particularly in the Dorsal Fin Spines (DFS). PCA analysis showed significant differences in morphometric characters but not supported by meristic characters. These results underscore the importance of integration both morphological and meristic analyses for a comprehensive understanding of the berod fish population.